Consumer attitude towards sustainable-labelled wine: an exploratory approach. Issue 4 (16th November 2015) - Sogari, Giovanni; Corbo, Chiara; Macconi, Martina; Menozzi, Davide; Mora, Cristina
Abstract : Purpose: – This paper aims to investigate, using an exploratory approach, how environmental values and beliefs about sustainable labelling shape consumer attitude towards sustainable wine. Design/methodology/approach: – Data were collected with an online survey from 495 Italian wine drinkers in 2013. The survey was advertised through websites, blogs, social networks and emails. Based on background research and literature review, ten hypotheses were tested. Then a structural equation model was constructed using latent variables to test the causal links specified in the model. Findings: – The results show that attitude towards sustainable-labelled wine is shaped by both environmental and quality beliefs about sustainable wine, while it is not affected by the economic dimension of sustainability. In addition, age appears to have a slight effect on attitude because young consumers seem to be more interested in sustainability aspects of food products than older people are. Practical implications: – The paper suggests that company communication strategies should focus on sustainable issues to meet the requirements of environmentally conscious consumers. At the same time, sustainable certification on wine labels may help wineries to become more competitive using verifiable sustainable claims to differentiate their products. Originality/value: – The work adds to the literature on wine marketing by evaluating which variables influence consumer attitude towards sustainable-labelled wine and, at the same time, to what extent sustainable aspects are important during wine purchase.